Pengaruh Manajemen Pendidikan Agama Kristen dalam Edukasi Keluarga Kristen di Jemaat Tengko Klasis Walendrang Timur - Nilka Nilka; Nensy Patabang; Tikayani Patodingan; Arlin Sidakka; Derli Kendek (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2025)
This study examines the impact of Christian Religious Education Management on the spiritual development and character formation of children in Christian families, especially in the Tengko Klasis Walendrang Timur Congregation. This study emphasizes the basic role of the family as the primary environment in instilling moral and spiritual values, despite challenges arising from the negative influences of technological advances and modern lifestyles. Using a quantitative approach and purposive sampling technique, this study assesses how parental guidance—with the support of church education programs such as Sunday School and Catechism—contributes to the formation of a strong Christian identity in children. The results of the study indicate that effective education management, in which parents act as educators, motivators, facilitators, mentors, and role models, is essential to fostering sustainable spiritual growth and positive character. This study concludes that increased collaboration between families and churches is needed to strengthen spiritual education so that children can develop mature and resilient Christian characters.